Dual Inoculation With Arbuscular Mycorrhizal Fungi and Phosphorus Solubilizing Fungi Synergistically Enhances the Mobilization and Plant Uptake of Phosphorus From Meat and Bone Meal - Jatana, Bhupinder Singh; Kitchens, Christopher; Ray, Christopher; Gerard, Patrick; Tharayil, Nishanth (Frontiers in Soil Science, 2021)
Phosphorus (P) is the second most important mineral nutrient for plant growth and plays a vital role in maintaining global food security. The natural phosphorus reserves [phosphate rock (PR)] are declining at an unprecedented rate, which will threaten the sustainable food supply in near future. Rendered animal byproducts such as meat and bone meal (MBM), could serve as a sustainable alternative to meet crop phosphorus demand. Even though nitrogen (N) from MBM is readily mineralized within a few days, >75% of the P in MBM is present as calcium phosphate that is sparingly available to plants. Thus, application of MBM with the aim of meeting crop N demand could result in buildup of P reserves in soil, which necessitates the need to improve the P mobilization from MBM to achieve higher plant P use efficiency. Here, we tested the potential of two microbial inoculum-arbuscular mycorrhizal fungi (AMF) and P solubilizing fungi (Penicillium bilaiae), in improving the mobilization of P from MBM and the subsequent P uptake by maize (Zea mays). Compared to the non-inoculated MBM control, the application of P. bilaiae increased the P mobilization from MBM by more than two-fold and decreased the content of calcium bound P in the soil by 26%. However, despite this mobilization, P. bilaiae did not increase the tissue content of P in maize. On the other hand, AMF inoculation with MBM increased the plant root, shoot biomass, and plant P uptake as compared to non-inoculated control, but did not decrease the calcium bound P fraction of the soil, indicating there was limited P mobilization. The simultaneous application of both AMF and P. bilaiae in association with MBM resulted in the highest tissue P uptake of maize with a concomitant decrease in the calcium bound P in the soil, indicating the complementary functional traits of AMF and P. bilaiae in plant P nutrition from MBM. Arbuscular mycorrhizal fungi inoculation with MBM also increased the plant photosynthesis rate (27%) and root phosphomonoesterase activity (40%), which signifies the AMF associated regulation of plant physiology. Collectively, our results demonstrate that P mobilization and uptake efficiency from MBM could be improved with the combined use of arbuscular mycorrhizal fungi and P. bilaiae.